Characteristics Of Master English Teachers In Thailand: A Case Study - Watthanaboon, Supanrigar (2006)
This case study attempted to investigate the notable characteristics and roles of two Thai Master English teachers in Nakhonsithammarat Province, Southern Thailand. The study investigated thoroughly the two case teachers including their administrators, peer teachers, school boards, and students who were involved with the case teachers either in the present or in the past Two methods of data collection, namely, the qualitative and quantitative approaches were employed. However, because of the nature of the study, more emphasis was done on the qualitative method from 34 interviews and 20 classroom observations of both the case teachers. The interviews and observations were triangulated by using the Likert Scale Questionnaire. The questionnaires captured the perceptions and observations of 473 current and past students of the two teachers. The qualitative data were analysed using the procedures outlined by Bogden and Biklen (1998); Gay & Airsian (2003) on data reduction and display. In order to validate the data and the analysis, the interpretative and crosschecking techniques for triangulation were conducted.